Upaya Kontra-Narkotika Amerika Serikat terhadap Ancaman Narkoterisme di Afghanistan - Febby Diah Papalangi; Christian Herman Johan de Fretes; Roberto Octavianus Cornelis Seba (Fakultas Ilmu Sosial dan Hukum, 2023)
After 9/11, Afghanistan became an important actor in U.S. policymaking. Not only does it bring the threat of terrorism, but also the danger of narcotics. UNODC noted that the cultivation of opium production as an illegal crop in Afghanistan has increased significantly since 2001. Until recently Afghanistan led global opium production. Despite numerous counter-narcotics efforts and strategies undertaken by the United States and the international community to reduce the amount of illegal crop production, the approach has not been effective enough, let alone the achievement of reconstruction and stability in the country. Through the perspective of liberalism, this article details U.S. counternarcotics efforts and challenges in Afghanistan.